Legal Aspects of the Capital Market Position and Benefits in Indonesia: A Comparative Study - Suhardini, Eni Dasuki; Suharno, Rachmat; Owen, Reynald Sandi (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Capital markets play a crucial role in the economic growth of many countries, including Indonesia and Malaysia. Capital markets raise funds and serve as investment instruments. Through various instruments, such as stocks, bonds, and mutual funds, investors need information to obtain a clear portfolio that makes them confident in investing their funds in Indonesia or Malaysia.Purposes of the Research: This study aimed to analyze the legal positions and benefits of capital markets in Indonesia and Malaysia.Methods of the Research: This study was legalistic, doctrinal, or normative, using a comparative law approach to compare the legal position and benefits of the capital market in Indonesia with Malaysia.Results of the Research: Capital markets are crucial in Indonesia's and Malaysia's economies. To protect market players, Indonesia issued Law Number 8 of 1995 on the Capital Market and related instruments, such as Law Number 4 of 2023 on Financial Sector Development and Strengthening and Law Number 21 of 2011 on the Financial Services Authority (OJK). Similarly, Malaysia issued the Capital Markets and Services Act of 2007 to provide legal certainty and increase investor confidence. The capital market significantly impacts economic growth in both countries, serving as a crucial component of the economic ecosystem by providing investment opportunities through corporate actions, such as initial public offerings, secondary share issuances, and bond offerings.